Future Population Exposure to Daytime and Nighttime Heat Waves in South Asia. Issue 5 (12th May 2022) - Ullah, Safi; You, Qinglong; Chen, Deliang; Sachindra, D. A.; AghaKouchak, Amir; Kang, Shichang; Li, Mingcai; Zhai, Panmao; Ullah, Waheed
Abstract: Climate change is expected to result in more frequent and intense heat waves (HWs) in South Asia (SA). The simultaneous increases in temperature and population will exacerbate the population exposure to future HWs. Here we estimate the future population exposure to daytime and nighttime HWs in SA using the Coupled Model Intercomparison Project 6 (CMIP6) models under four Shared Socioeconomic Pathways (SSPs) during 2061–2100, relative to 1975–2014. The results show that the projected frequency and spatial extent of the daytime (nighttime) HWs will be higher under scenario SSP5‐8.5, followed by SSP2‐4.5, SSP3‐7.0, and SSP1‐2.6 (SSP5‐8.5, followed by SSP3‐7.0, SSP2‐4.5, and SSP1‐2.6), relative to the historical period. The approach presented here allows decomposing the effects of climate change and future population on the overall exposure. The results reveal that the compounding effects of projected trends in population and HWs will significantly escalate the population exposure to HWs. Under the selected SSPs, the total population exposure to daytime and nighttime HWs ranges from 185 to 492 and 204–555 million people‐event, respectively, with the maximum exposure occurring in the Indo‐Gigantic Plain. The wide range of exposed populations highlights the sensitivity of the overall exposure to our future socioeconomic pathway decisions, emphasizing the importance of curbing anthropogenic greenhouse gas emissions and adopting sustainable urban planning solutions to minimize the potential socioeconomic and health impacts of HWs. Plain Language Summary: Climate change will intensify the occurrence and intensity of heatwaves (HWs) in South Asia, with severe impacts on the population. Here we estimate the population exposure to daytime and nighttime HWs using the Coupled Model Intercomparison Project 6 (CMIP6) models under four Shared Socioeconomic Pathways (SSPs). The results show that the projected daytime and nighttime HWs will impact around 185–492 and 204–555 million people under the selected SSPs, respectively, with the maximum exposure occurring in the Indo‐Gigantic Plain. The wide range of populations under different SSPs highlights the sensitivity of the population to future SSP decisions. This emphasizes the importance of reducing greenhouse gas emissions and adopting sustainable urban planning solutions to minimize the potential socioeconomic and health impacts of HWs. Key Points: The number and extent of heat waves (HWs) are projected to increase under all the Shared Socioeconomic Pathways (SSPs) The population exposure to HWs ranges from 185 to 555 million people‐event with the highest exposure in the Indo‐Gigantic Plain Compounding effects of climate change and population increase substantially aggravate exposure to HWs